Effect of a Single Standard Dose (150–200 μg/kg) of Ivermectin on Loa loa Microfilaremia: Systematic Review and Meta-analysis. (11th January 2019) - Pion, Sébastien D; Tchatchueng-Mbougua, Jules Brice; Chesnais, Cédric B; Kamgno, Joseph; Gardon, Jacques; Chippaux, Jean-Philippe; Ranque, Stéphane; Ernould, Jean-Christophe; Garcia, André; Boussinesq, Michel
Abstract: Background: In central Africa, millions of individuals infected with Loa loa have received the anthelminthic drug ivermectin (IVM) as part of mass drug administration (MDA) campaigns targeting onchocerciasis control or elimination. Nonetheless, the parasitological surveys that are occasionally conducted to evaluate the impact of IVM treatments on Onchocerca volvulus do not include an assessment of the extra benefits of those MDA campaigns on L. loa . Methods: We conducted a systematic review of trials on the effect of a single standard (150–200 μg/kg) dose of IVM on L. loa microfilarial density (MFD). The dynamics of MFD over 365 days of treatment were described using multilevel regression and latent class modeling. Results: IVM brings about a rapid, dramatic, and sustained decrease, with reduction rates of 60%, 75%, 85%, and 90% on day 1 (D1), D2, D7, and D365, respectively. At D365, no participants (0/238) with an initial MFD of <20 000 microfilariae (mf)/mL were at risk of postivermectin severe adverse events, and only 1/57 individuals with an initial MFD of ≥20 000 mf/mL presented with an MFD above this value. The main predictor of post-treatment MFD was the pretreatment value, but this post-treatment value varied little between D8 and D365 regardless of the pretreatment level. Conclusions: A single dose of IVM is very effective at substantially reducing L. loa MFD for at least a year, irrespective of the initial level of parasitemia. Individuals treated with IVM are probably not any more at risk of severe adverse events when retreated 1 year later.